Measuring the Impact of Demographic Transition on the Sustainability of the Pension System in Algeria using the Theory of Co-Integration - Larbi Cherif, Hadjira (جامعة أمحمد بوقرة بومرداس - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - مخبر مستقبل الأقتصاد الجزائري خارج المحروقات, 2021)
تهدف هذه الدراسة إلى قياس تأثير العوامل الديمغرافية المتمثلة في معدلات الخصوبة وتوقع الحياة في خلق العجز المالي لنظام التقاعد في الجزائر، باستخدام اختبار التكامل المشترك ونموذج الانحدار الذاتي ذو المبطئات الموزعة ARDL. وأثبتت النتائج أن الصندوق الوطني للتقاعد يعاني من عجز مالي متزايد منذ سنة 2013، كما أثبت اختبار التكامل المشترك وجود علاقة مستقرة طوية الأجل بين نسبة الرصيد المالي لصندوق للتقاعد/ GDP وتوقع الحياة ومعدلات الخصوبة، وهذه العلاقة سالبة مما يعني أن بتزايد العمر المتوقع عند الولادة يتزايد عدد المتقاعدين نسبة إلى عدد المشتركين في الضمان الاجتماعي مما يؤدي إلى زيادة عجز الصندوق الوطني للتقاعد.
The objective of this study is to determine the extent to which demographic factors (fertility rate and life expectancy) contribute to the creation of the pension system deficit in Algeria, based on the results of the estimation long-term relationships using the co-integration test and the ARDL model for the period (1995-2019). The results of the co-integration test showed a long-term steady-state relationship between the ratio of CNR balance/GDP, life expectancy and fertility rates, which is negative, as life expectancy increases, the number of pensioners increases relative to the number of social security contributors, resulting in an increase in the deficit of the CNR.
Keywords: نظم المعاشات -- التأمينات الاجتماعية -- الضمان الاجتماعى